DIAGNOSIS DAN PENATALAKSANAAN HYPEROSMOLAR HYPERGLYCEMIC STATE (HHS) (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2019)
ABSTRACT Introduction: The Hyperosmolar Hyperglycemic State (HHS) is rare case and the most serious acute hyperglycemic emergency in patients with type 2 diabetes, are characterized by severe hyperglycemia, hyperosmolality, and dehydration in the absence of ketoacidosis. Guidelines on the management of hyperglycaemic hyperosmolar state (HHS) in adults are uncommon and often there is little to differentiate them from the management of ketoacidosis diabetic, but HHS is different and treatment requires a different approach. Immediately treatment is necessary to reinstate hemodynamic stability, as mortality rates for HHS are exceptionally high and can have multiple complications Keywords: Diabetes Mellitus, Hyperosmolar Hyperglycemic State, Hyperglycemia ABSTRAK Latar Belakang: Hyperosmolar Hyperglycemic State (HHS) merupakan kasus yang jarang dan komplikasi emergensi akut dari pasien diabetes melitus tipe 2, dengan karakteristik hiperglikemi, hiperosmolar dan dehidrasi atau tidak adanya ketoasidosis. Pedoman manajemen hiperglikemia hiperosmolar (HHS) pada orang dewasa tidak umum dan berbeda dengan manajemen ketoasidosis diabetik. Tatalaksana segera penting dilakukan untuk menstabilkan hemodinamik, mortalitas dari HHS tinggi dan dapat menyebabkan banyak komplikasi. Kata Kunci : Diabetes Melitus, Hyperglycemic Hyperosmolar State, Hiperglikemi